Morphology and Morfometric Study of Crabs Species Caught on the Coast of Mokupa, Minahasa District, North Sulawesi - Pelafu, Widya; Paransa, Darus Saadah J.; Mantiri, Desy M. H; Kemer, Kurniati; Bara, Robert A.; Batarogoa, Nego E. (Sam Ratulangi University, 2022)
Crabs are organisms that have been found moving actively in tidal areas. One is in the coastal area of Mokupa, Whare the study boasts a great diversity of poorly informed crabs. this study aims to identify the morphology and diversity of crab species during the full moon and late nephew phase. The location for sampling is on the coast of Mokupa Beach, Minahasa Regency, North Sulawesi. This research was conducted using the roaming method and captured directly at night at the lowest low tide based on the phases of the full moon and late nephew. Furthermore, the collected crabs were identified by morphology, body length, body color, carapace shape, pair of claws, walking legs, and abdomen, and morphometric calculations were performed. Based on the morphological identification found, namely: Thalamita crenata, Geograpsus crinipes, Selatium brocki, and Sesarmops impressus.Keywords: Coastal beaches, Morphology, Crab type. AbstrakKepiting merupakan organisme yang ditemukan bergerak aktif di daerah pasang surut. Salah satunya di daerah pesisir Pantai Mokupa, lokasi ini memiliki banyak keanekaragaan jenis kepiting yang belum terinfomasi dengan baik. Penelitian ini bertujuan mengidentifikasi morfologi dan keanekaragaman jenis kepiting saat fase bulan purnama dan perbani akhir. Lokasi penangkapan sampel di pesisir Pantai Mokupa, Kabupaten Minahasa.Sulawesi Utara, dilakukan mengunakan metode jelajah dan ditangkap langsung pada waktu malam hari saat surut terendah berdasarkan fase bulan purnama dan perbani akhir. Selanjutnya, kepiting yang yang terkumpul diidentifikasi morfologi diamati ukuran panjang tubuh, warna tubuh, bentuk karapas, sepasang capit, kaki jalan dan abdomen, serta dilakukan perhitungan morfometrik. Berdasarkan identifikasi morfologi ditemukan, yaitu: Thalamita crenata, Geograpsus crinipes, Selatium brocki dan Sesarmops impressus. Kata kunci: Pesisir pantai, Morfologi, Jenis kepiting.